Exploring demographic disparities in the mastery of higher-order thinking skills among primary school pupils - Yee Mei Heong, Yee Mei Heong; Mahmad, Mohd Faisal; Tee Tze Kiong, Tee Tze Kiong; Kok Boon Ching, Kok Boon Ching; Azid, Nurulwahida; Nur Rahma Putra, Andika Bagus (2024)
Today's pupils should cultivate higher-order thinking skills (HOTS) more than anything else. This study aims to assess the HOTS level among primary school pupils based on demographics and their differences. The population in this study included all Year 5 pupils at primary school in Malacca. Malaysia. A total of 73 pupils from a primary school in Malacca, Malaysia were selected as research samples. The SEA test (Synthesis, Evaluation and Analysis) was modified to collect research findings. Data were analyzed descriptively and inferentially using SPSS software and presented into mean, frequency, and percentage. The findings showed that most primary pupils have a very low level of HOTS based on gender and socioeconomics (SES). T-test analysis showed that there was no significant difference in the mean scores of HOTS level between male and female pupils. However, there was a significant difference in the mean scores of HOTS level based on SES. In conclusion, to support pupils' HOTS abilities, the HOTS instruction should cultivate reasoning and problem-solving techniques rather than procedural fluency.